Psychotherapy in later life - Tampi, Rajesh R. 1970-; Yarns, Brandon ca. 20./21. Jh; Zdanys, Kristina F. ca. 20./21. Jh; Tampi, Deena J. ca. 20./21. Jh (Cambridge University Press, 2020)
Psychotherapy in Later Life is a practical how-to-guide for psychiatrists, psychologists and mental health workers on choosing and delivering evidence-based psychological therapies to older adults. It covers all the main evidence-based psychological therapies such as cognitive behavioural therapy (CBT) and interpersonal psychotherapy (IPT), as well as specialist topics such as combining psychotherapy with pharmacological treatments, working with diverse populations and individual versus group therapy. The World Health Organization estimates that over the next four decades, the proportion of the world's older adults will nearly double, from twelve percent to twenty-two percent, and that one in five older adults has a diagnosable mental health disorder. Given the increasing number of older adults requiring mental health treatment, incorporating talking therapies into treatment plans is key to tackling issues related to polypharmacy, medication interactions and side effects. Written by experts in geriatric mental health, this book provides the most authoritative information on the use of psychotherapy in older adults
Title from publisher's bibliographic system (viewed on 15 Jan 2020)
Introduction to psychotherapy with older adults / Erica Garcia-Pittman, Victor Gonzalez, Anh-Thu Tran, Christine Dozier -- Indications for psychotherapy with older adults / Danielle Tolton, Tyler Durns, Sarah A. Nguyen, Neha Jain -- Choice of psychotherapy approach / Feyza Marouf -- Cognitive behavioral therapy / Patricia Bamonti, Lindsey Jacobs -- Problem-solving therapy / Brenna N. Renn, Brittany A. Mosser, Patrick J. Raue -- Interpersonal therapy / Mark D. Miller, Richard K. Morycz -- Short-term psychodynamic therapy / Patricia Coughlin, Brandon Yarns -- Other therapies / Renz Juaneza, Nery Diaz, Pallavi Joshi -- Psychotherapy and cognitive disorders / Cynthia Kraus-Schuman, Melissa Sanchez, Karen Benson, Ali Abbas Asghar-Ali -- Combined psychotherapy and medication management / Meera Balasubramaniam, Deepti Anbarasan, Paul Campion -- Psychotherapy with diverse older adults / Sarah A. Nguyen, Philip Blumenshine, Boski Patel -- Individual versus group psychotherapy / Paroma Mitra -- End of life issues / Sandra Swantek, James Gerhart
Keywords: Psychotherapy for older people; Older people / Mental health; Älterer Mensch; Psychotherapie; Aufsatzsammlung